Effect of different biofertilizer strains on soil, leaf and yield parameters of Kinnow mandarin - VIJAY; SOURABH; RANA, G S; DALAL, R P S; KUMAR, RAKESH; PREETI; KUMAR, AJAY (The Indian Journal of Agricultural Sciences, 2023)
Present field study was carried out to investigate the effects of biofertilizer strains on soil, leaf and yield parameters of Kinnow zandarin (C. nobilis × C. deliciosa) during 2018–19 and 2019–20 at the experimental orchard of Department of Horticulture, Chaudhary Charan Singh Haryana Agricultural University, Hisar, Haryana. The study revealed that soil, leaf nutrient status and yield parameters were significantly affected with the application of biofertilizers. There was synergistic influence of Azotobacter and PSB strains. The magnitude of increase with the application of different bio-strains was more pronounced when applied in combination with lower dose of fertilizers (75% RDF) than their combination with higher dose (100% RDF). 100% RDF + Azotobacter chroococcum Mac 27 + Pseudomonas P 36 (T7) was found most effective in enhancing soil macro-micro nutrients, leaf nutrient status and yield parameters. Soil available N and P increased significantly in 0–15 cm soil layer during both years but in 15–30 cm soil layer, the enhancement was observed only during second year of investigation, however Fe, Zn and Mn showed significant improvement only in 0–15 cm soil layer during both years. Leaf N content increased in September, however no significant effect was observed in March values. Leaf N content showed fast increment as compared to leaf P content.